Analysis Of Open Selection Mechanism In The Government Of Bantul District 2016 - Vindhi Putri Pratiwi; Muhammad Eko Atmojo; Awang Darumurti; Dyah Mutiarin; Helen Dian Fridayani (Universitas Muhammadiyah Ponorogo, 2021)
The purpose of this research is to see the open selection mechanism in the government of Bantul district. Because the success of bureaucratic reform is a part of human resources within the government bureaucracy. Therefore it is necessary to have human resource management to realize a state of civil apparatus with integrity, professionalism and competence. In this study, researchers used qualitative approach methods. Where in the technique is done in-depth interviews to get information and gather other supporting documents on this research. Human resource management could be done by structuring employees through an open selection mechanism. The Government of Bantul District has conducted an open selection in structuring employees who are in their government. Because the open selection is considered a solution in the screening of the state civil apparatus. Moreover, the Bantul Government in the open selection process uses several stages including administration selection, competency tests, interviews, and paper presentations. With the existence of several stages carried out in the open selection process by the Bantul Government, it is expected to capture and create a state civil apparatus who are professional and competent in running of bureaucracy in the government. So the existence of the state civil apparatus competent then will be influenced in its performance.